Waste disposal system in Shah Alam municipality / Mashod Katmin - Katmin, Mashod (Faculty of Mechanical Engineering, 1998)
One of the most pressing problems facing municipalities is the efficient and long term disposal of waste disposal. The waste disposal has become an issue of immense proportions. More and more these problems are news, with the political concerns overshadowing the technical and economic issues. Human activities generate wastes that are often discarded because they are considered useless. These wastes are normally and the meaning of the word waste suggests that the material is useless and unwanted. But, many of these waste materials can be reused and thus, can become a resource for industrial production or energy generation, if properly manage. The community that protect the health and safety of its residents and is clean and attractive must have an efficient, well organized refuse disposal system. Without one, disease carrying rats, flies and insects bound, water and air become polluted, fire hazard increased, unpleasant odors are common and streets, parkways, lots and alleys are littered and unattractive. As the population of Shah Alam increases and more and more people are concentrated in municipal areas, the more acute the problems grows. Futhermore, as standard of living go up, the public demands better waste disposal service. At the same thing, the higher standard of living complicated the problem by increasing the amount of waste disposal.